2018
DOI: 10.3389/fmicb.2018.02627
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiota in Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is an autoimmune-mediated disorder, the etiology of which involves both environmental factors and genetics. While the exact factors responsible for predisposition to MG remain elusive, it is hypothesized that gut microbiota play a critical role in the pathogenesis of MG. This study investigated whether gut microbiota are altered in MG patients by comparing the fecal microbiota profiles of MG patients to those of age- and sex-matched healthy controls. Phylotype profiles of gut microbial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 61 publications
11
89
3
1
Order By: Relevance
“…Qiu et al. [ 171 ], observed a sharp decrease in microbial diversity and significantly low levels of short chain fatty acids in MG patients. The ratio of Firmicutes - Bacteroidetes was significantly lower in MG patients than in controls, thus leading to a pro-inflammatory environment that damaged the intestinal epithelium.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Qiu et al. [ 171 ], observed a sharp decrease in microbial diversity and significantly low levels of short chain fatty acids in MG patients. The ratio of Firmicutes - Bacteroidetes was significantly lower in MG patients than in controls, thus leading to a pro-inflammatory environment that damaged the intestinal epithelium.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Myasthenia gravis (MG) is an autoimmune disease caused by autoantibodies that target the neuromuscular junction (NMJ), leading to partial or systemic muscle weakness and abnormal fatigability (Gilhus et al, 2016). Based on the location of the affected muscles, patients with MG are classified as ocular (OMG) or generalized MG (GMG) (Qiu et al, 2018). Ocular myasthenia gravis (OMG) is distinguished by fatigable weakness of the extraocular muscles, eyelids, or both, leading to fatigable ptosis and diplopia (Vaphiades et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, mounting evidences have shown that gut microbiota plays a crucial role in the onset of central [e.g., autism spectrum disorder ( Hsiao et al, 2013 ; Sharon et al, 2019 )] and peripheral [e.g., irritable bowel syndrome ( Duerkop et al, 2018 )] diseases. Meanwhile, previous studies have found that gut microbial disorders may attribute to the onset of MG patients through fecal metabolism ( Qiu et al, 2018 ; Zheng et al, 2019a ). For instance, previous studies have observed that patients with MG showed a decrease in α-phylogenetic diversity, and significantly altered gut microbiome and fecal metabolome.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome is part of a complex ecosystem. Gut microbiota have a mutualistic relationship with their host and play a crucial role in maintaining the host's health . It is now well documented that gut microbiota modulate adiposity via various mechanisms, such as lipopolysaccharide (LPS)‐induced chronic inflammation, gut‐derived peptide secretion, and modulation of tissue fatty acid composition .…”
Section: Introductionmentioning
confidence: 99%